Effect of laser shock peening without coating (LPwC) on a surface and sub-surface characteristics of aged Ti 15 V-3Al- 3Cr-3Sn alloy. (2021) - Jose, Bibin; Patil, Tejas; Sudhagara Rajan, S.; Praveenkumar, K.; Manivasagam, Geetha; Swaroop, S.
Abstract: This paper investigates the effect of Laser Shock Peening without Coating (LPwC) on the surface and sub-surface (i.e. residual stress, hardness in-depth direction surface roughness) of a β-Ti alloy Ti- 15 V-3Cr-3Al-3Sn (Ti-15–3) in duplex aged condition. Duplex aging was carried out at 250 °C for 24 h, followed by treatment at 500 °C for 8 h. LPwC was performed using an Nd :YAG laser with three distinct parameters. The effect of LPwC was analysed using roughness profilometer, X-Ray diffraction and microhardness tester. The obtained results and discussions were elaborated.